Growth and Development of Winged Bean (Psophocarpus tetragonolobus (L.) DC.) Treated with Paclobutrazol - Wijayanti, Jihan Sekar; Dewi, Kumala (Journal of Tropical Biodiversity and Biotechnology, 2024)
Winged bean (Psophocarpus tetragonolobus (L.) DC.) is one of the tropical legumes commonly grown for vegetable in Indonesia. Winged bean is a kind of plants that growth on vine so that for cultivation it requires stakes or awnings. It is known that paclobutrazol is a growth retardant that acts by inhibiting gibberellin biosynthesis and application of paclobutrazol could make plant become semidwarf or even dwarf. This study was aimed to evaluate the effect of paclobutrazol on growth, development, some phytochemicals content and yield of winged bean plants. This study used a Completely Randomized Design (CRD) with one factor, namely paclobutrazol, which was applied at four different concentrations, namely 0 ppm (control), 25 ppm, 50 ppm, 75 ppm or 100 ppm. Three replicates were made for each treatment. The results showed that paclobutrazol significantly decreased plant height, number of leaves, leaf area, number of pods per plant, pod length, fresh weight of fruit, levels of vitamin C and protein in the pods, but increased the leaf chlorophyll content and stomata density on the abaxial (lower) leaf surfaces. Paclobutrazol showed its effect on accelerating flowering time at a concentration of 50 ppm.